The Balance of Interests in the Coexistence of Homonymous Geographical Indications: Suggestions for Practical International Implementation - Jimenez Garay, Andrea (2025)
This paper explores the coexistence of homonymous geographical indications (GIs) in the absence of explicit internationally harmonized provisions regulating this issue in general. It aims to identify the challenges or problems arising from such coexistence and to delineate the conditions under which it might be allowed, while maintaining a balance among the interests of producers, consumers, and States (public interest). To achieve this, the paper conducts an inductive analysis of the coexistence of the homonymous GI for grape distillates: “Pisco”, claimed by both the Republic of Chile and the Republic of Peru. This analysis has revealed these three challenges arising from the coexistence: a) consumers’ confusion, b) ambiguous international protection, and c) erosion of the GI’s economic value as a marketing tool, which may give rise to other problematic consequences. Then, these three issues are analyzed in-depth from a theoretical standpoint, applying some of the principles of the trademark system by analogy. The paper ultimately concludes that coexistence should be allowed as an exception, provided that the GIs’ distinctiveness is not diluted, and consumers are neither confused nor misled. Bulding on this analysis, the paper proposes a systematic interpretation of the TRIPS Agreement provisions to address the issue of the coexistence of homonymous GIs. This suggested interpretation could lead to a redrafting of Articles 22 and 23 of the TRIPS Agreement, according to the terms outlined within this paper. Furthermore, it could be considered in negotiations of bilateral or plurilateral trade agreements in which States mutually recognize each other’s GIs. To facilitate the latter, the paper advances a possible model clause that States can consider adopting.